The status of career awareness among selected Kenyan public secondary school students - Ibrahim, Racho; Wambiya, Pascal; Aloka, Peter J. O.; Raburu, Pamela A. (MCSER, 2014)
The study investigated the status of career awareness among public secondary school students in Marsabit Central district, Kenya. The study adopted descriptive survey design. The target population of students was 2,259, nine guidance and counselling teachers. 250 students in the district were selected using stratified sampling technique. Six guidance and counselling teachers representing 67% of the 9 guidance and counselling teachers in the district were also randomly selected for the study. The researcher used questionnaires and interviews to elicit information from students and interview schedules to collect data from counselling teachers and principals. The findings indicated that, students’ career awareness had significant relationship with students’, (Ȥ2=56.250, df=49, p=0.001<0.05) career decisions. That is, the students who were aware of careers were able to make career decisions, while those who were not aware of careers had difficulty making career decisions. This implies that effective career guidance and counselling could help students to be aware of careers and this enabled them to be able to make right career decisions. The study recommended that school counsellors should provide a systematic approach to helping all students with the decision making process, to understand; themselves and to develop appropriate goals through the interpretation of standardized test results and course performance.
Doi:10.5901/jesr.2014.v4n6p301
Keywords: Status; Career awareness; Kenyan; Public; Secondary school; students